Afrocentric beauty: The proliferation of ‘Texturist’ and ‘Colorist’ beliefs among young women in Kenya - Karen Mwende Kinuthia; Emy Susanti; Stacy Pamba Kokonya (Faculty of Social and Political Science, Universitas Airlangga, 2023)
The beauty ideals of a Eurocentric nature have been promulgated among African communities for decades dating back to the colonial era. The beauty ideal posits lighter or brown skin tone as prettier and straight hair as attractive. The study aimed to identify ways in which families and peers have perpetuated this common beauty ideal within the home and school settings and how these have influenced how young women view themselves. There were 20 young women of different skin tones ranging from light, medium (brown) to dark participated in two focus group discussions. Thematic analysis was used whereby three main themes (familial influence, peer socialization and self-perceptions) and four sub-themes were identified (general opinion, teasing, family disassociation and preferential vs. unfair treatment). Findings revealed that family member and peers knowingly and unknowingly augmented ‘colorist’ and ‘texturist’ beliefs by ridiculing both dark-skinned and light-skinned women. Most of them treated dark skinned people unfairly. The research findings suggested that future research should investigate how body features represent attractiveness within the African communities.